DEMOKRASI ELEKTORAL DALAM KENDALI KUASA OLIGARKI KABUPATEN ACEH TENGGARA PROVINSI ACEH - Mustapa Kamil Alga Beruh; Lusiana Lusiana (ADISAM PUBLISHER, 2025)
Electoral democracy under oligarchic control is a phenomenon where the electoral process is influenced or dominated by a small group of individuals wielding significant economic or political power. This study aims to analyze the characteristics, impacts, and potential solutions for overcoming oligarchic control in electoral democracy, specifically in Southeast Aceh Regency. The findings reveal that electoral democracy in Southeast Aceh faces substantial challenges due to the strong influence of oligarchs, which can undermine the quality of democracy and increase public dissatisfaction. To address these challenges in the long term, implementing effective solutions can help foster a healthier and more robust electoral democracy in Southeast Aceh, enabling citizens to better exercise their political and economic rights. Therefore, concerted efforts are necessary to implement these solutions and enhance the overall quality of democracy in the region